BLOCK CHAIN DRIVEN SUPPLY CHAIN SECURITY: INTEGRATING POST QUANTUM CRYPTOGRAPHY WITH AES - Eaman Raza Rizvi,; Shahzada Khurram, (Spectrum of Engineering Sciences, 2025)
Conventional cryptographic methods are gravely threatened by the development of quantum computing consequently, post quantum cryptographic (PQC) methods must be applied to secure data flow. In this work, we propose a hybrid encryption strategy based on Advanced Encryption Standard (AES) and Kyber, a lattice based PQC method, to raise the safety and processing efficiency of block chain systems, including multi stakeholders. Kyber codes keys Advanced Encryption Standard (AES) encrypts data. This approach lowers processing delay and is post quantum safe. Based on a performance study, the RSA encryption procedure takes 0.00049 seconds, and the decryption process takes 0.003051 seconds, therefore producing a total delay of 0.003524 seconds. Advanced Encryption Standard (AES) is quite efficient in generating a total delay of 0.000022 seconds, given a decryption time of 0.00001 seconds and an encryption time of 0.000012 seconds. The PQC hybrid (Kyber + AES) model helps one to reach these numbers with an encryption time of 0.0012 seconds, a decryption time of 0.0015 seconds, and a total processing delay of 0.002 seconds. This approach allows one to strike a compromise between real time communication effectiveness and safety. Research findings highlight the relevance of the concept in post quantum block chain systems, decentralized networks, and safe multiple party transactions, all settings where data integrity and secrecy are paramount. The paper presents a novelty in that it proved the existence of a hybrid encryption technique resistant to pragmatic and quantum computers.